Interrogating metabolism as an electron flow system. Issue 13 (February 2019) - Zerfaß, Christian; Asally, Munehiro; Soyer, Orkun S.
Abstract: Metabolism is generally considered as a neatly organised system of modular pathways, shaped by evolution under selection for optimal cellular growth. This view falls short of explaining and predicting a number of key observations about the structure and dynamics of metabolism. We highlight these limitations of a pathway-centric view on metabolism and summarise studies suggesting how these could be overcome by viewing metabolism as a thermodynamically and kinetically constrained, dynamical flow system. Such a systems-level, first-principles based view of metabolism can open up new avenues of metabolic engineering and cures for metabolic diseases and allow better insights to a myriad of physiological processes that are ultimately linked to metabolism. Towards further developing this view, we call for a closer interaction among physical and biological disciplines and an increased use of electrochemical and biophysical approaches to interrogate cellular metabolism together with the microenvironment in which it exists. Highlights: Cell metabolism represents an interconnected network rather than isolated pathways. Capturing the interconnected nature of metabolism makes experimental and theoretical analysis of metabolism very challenging. We highlight kinetic and thermodynamic constraints arising from a view of metabolism as an electron flow as a fundamental approach to study and understand metabolism. We call for the development of experimental tools and models that focus on capturing redox and ion fluxes connected to electron flows through metabolism.